Inverse proportion : a constructivist view of college students / Beh Kian Lim, Tong Swee Foong and Che Noorlia Noor - Beh, Kian Lim; Tong, Swee Foong; Noor, Che Noorlia (Research Management Institute (RMI), 2008)
From the constructivist paradigm, knowing misconceptions of students regarding a particular concept is deemed vital in designing effective instruction. Ausubel (1968) commented that 'The most important single factor influencing learning is what the learner already knows; ascertain this and teach him accordingly'. The symbiosis between science and mathematics is a profound one. Science views mathematics as a significant branch. Science likes to refer mathematics as the Queen, as mathematics nurtures the growth of science especially in the areas such as scientific prediction and manipulation. On the other hand, many concepts of mathematics are invented for the purpose of science such Proportion and Calculus to name a few. Two major ideas in Proportion are the Direct and the Inverse. A good grasp of these mathematical ideas is paramount for students in understanding the fundamental nature of science in its quantitative form. This paper offers a comprehensive description of seven hundred and fifty nine science based students (385 female and 374 male) from a local university in their developmental understanding of this mathematical idea of Inverse Proportion from the six domains i.e., Definition of Inverse Proportion, Graphical Representation of Inverse Proportion, Mathematical Representation of Inverse Proportion, Data Characteristic of Inverse Proportion, Relational Understanding of Inverse Proportion, and Problem Solving in Inverse Proportion. It discusses these six domains from two perspectives i.e., Academic Ability and Gender. The paper is based on a study by Beh et al (2008) anchoring on Constructivism. Among the major findings are: Students irrespective of high or low academic ability generally performed poorly in domains requiring conceptual understanding but showed relatively higher competency for the domain requiring procedural skills. Students of higher level academic ability demonstrate a significant in dept understanding of Inverse Proportion than students of lower level of academic ability; and Male students overall understanding of Inverse is significantly higher than their female counterparts at the 5% level. Since the study is based on Constructivism, it also highlights students' alternative frameworks. Implications for teaching and learning will be discussed.